Complete metabolic response (CMR) in positron emission tomography–computed tomography (PET‐CT) scans may have prognostic significance in patients with marginal zone lymphomas (MZL). Issue 1 (11th April 2017) - Park, Ji Hyun; Kim, Shin; Ryu, Jin Sook; Lee, Sang‐wook; Park, Chan‐sik; Huh, Jooryung; Suh, Cheolwon
Abstract: Although clinical use of positron emission tomography–computed tomography (PET‐CT) scans is well established in aggressive lymphomas, its prognostic value in marginal zone lymphoma (MZL) remains yet unclear. Hence, we investigated potential role of PET‐CT in predicting MZL patients' outcomes following systemic chemotherapy. A total of 32 patients with MZL who received first‐line chemotherapy were included in the analysis. They all underwent pretreatment, interim, and posttreatment PET‐CT scans. The primary objective was to evaluate the role of complete metabolic response (CMR) in posttreatment PET‐CT scans in predicting progression‐free survival (PFS). Compared with non‐CMR group, 5‐year PFS rate was significantly higher in patients who achieved CMR in posttreatment PET‐CT (54.2% vs 0.0%, P  = .003) and also in patients gaining CMR in interim PET‐CT scans (62.5% vs 15.6%, P  = .026). Interestingly, early CMR group, who achieved and maintained CMR in both interim and posttreatment PET‐CT scans, showed significantly higher 5‐year PFS than those with delayed or never CMR group (62.5% vs 37.5% vs 0%, P  = .008). Therefore, interim and/or posttreatment CMR can be prognostic at least in these subsets of patients with MZL treated with chemotherapy.